Musical Composition “Manggaro Yuk” Representation of "Manggaro" Cultural Activities in Minangkabau - Andika, Yuhari; Muchtar, Asril (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The musical composition "Manggaro Yuk" is inspired by the "manggaro" cultural activities of the farming community of Padang Panjang city. The musical composition uses traditional Minangkabau music idioms such as talempong pacik, gandang tambua, typical Minangkabau dendang (vocals), and bamboo and cans filled with gravel, then adapted to the dialect and culture of the people of Tanah Datar Regency and Padang Panjang City. This work was displayed at the final lesson of the Central Ministry of Education, Culture and Research and Technology's Movement for Artists Entering Schools (GSMS) program together with the Padang Panjang City Education and Culture Office in 2023 by 20 (twenty) students of Hikmah Middle School in Padang Panjang City. Qualitative methods are used for data collection, reflection, observation, and interviews. The workart is carried out in four stages, namely: preparation, incubation (contemplation or incubation), lighting, and verification. The work "Manggaro Yuk" is divided into three parts which are the author's representation of the problems and phenomena experienced by farmers in Minangkabau expressed through Minangkabau instruments and non-conventional instruments.